My hart kry swaar: reconsidering patriarchy through queer abstraction, phenomenology and the haptic - Van Der Vloed, Miro (Michaelis School of Fine Art, 2026)
My Hart Kry Swaar consists of an exhibition of sculpture, print, sound, and an explicatory document. The research project explores how the physicality of working with materials such as clay, wood and felted wool centre the body and movement as having the potential to release and process latent traumatic experiences and memories. The body-focused methodologies employed in producing the work include sculpting organic forms, wedging clay, impression moulding parts of my body, mark making and performance; all of which foregrounds the presence and absence of human touch. Conceptually the artwork and text critically engage with the pervasive influence of patriarchal ideology, specifically from a queer and personal perspective, contextualised within Afrikaner culture in South Africa. Key theoretical concerns include queer abstraction, narratology, phenomenology, hapticity and kinship, which highlight the need for envisioning alternatives to patriarchal masculinity. The role of tactile engagement with materiality, impermanence and strategies of queer abstraction are foregrounded in resisting binary and heteronormative classification, as well as imagining new narratives of desire and belonging. The project is situated within the fluctuating temporal boundaries of queer narratology, referencing theorists such as Florian Zitzelsberger, Sara Ahmed, Jack Halberstam, David Getsy, José Esteban Muñoz, Laura Berlant, and Kath Weston to investigate the relational complexities between the self, biological family, and queer chosen family. Both the practical and theoretical components of the project foreground the importance of queer narratives and fostering safe communities in order to resist and re-imagine existing hegemonic narratives around intimacy and the body.